2020
DOI: 10.1055/s-0040-1716836
|View full text |Cite
|
Sign up to set email alerts
|

Stage 4S Neuroblastoma: What Are the Outcomes? A Systematic Review of Published Studies

Abstract: Introduction The prognosis of stage 4S/MS neuroblastoma has traditionally been reported as excellent, yet conflicting treatment protocols exist for this enigmatic disease. To critically address this question, we have undertaken a systematic review of published studies to accurately determine outcomes for infants with stage 4S/MS neuroblastoma. Materials and Methods Studies were identified using MEDLINE, Embase, and Cochrane databases using the relevant search terms. Literature reviews, case reports, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Abdominal wall defects (AWDs), notably gastroschisis and omphalocele, are relatively rare congenital anomalies with a prevalence of 1.85 and 1.96 per 10,000 births in Finland, respectively [ 1 , 2 ]. Total prevalence of these anomalies has increased in Finland since previous rates published in 1980s [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abdominal wall defects (AWDs), notably gastroschisis and omphalocele, are relatively rare congenital anomalies with a prevalence of 1.85 and 1.96 per 10,000 births in Finland, respectively [ 1 , 2 ]. Total prevalence of these anomalies has increased in Finland since previous rates published in 1980s [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total prevalence of these anomalies has increased in Finland since previous rates published in 1980s [ 3 ]. Due to over 50% termination rate for omphalocele, however, increased live birth prevalence has only been observed in gastroschisis [ 1 , 2 ]. In most cases, gastroschisis in an isolated anomaly [ 1 , 4 , 5 ], whereas omphalocele is often associated with other severe anomalies including chromosomal abnormalities and cardiac defects [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review on the outcome of stage 4S neuroblastoma confirmed that significant mortality is still observed in these patients, and that those with MYCN gene amplification and 1p/11q deletion have a dismal outcome [31]. The authors concluded that patients amenable to conservative management or surgery to excise the primary tumor have the best prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of MYCN oncoprotein is strongly associated with rapid disease progression and poor outcome in patients independent of age and tumour staging 4,5 . Other chromosomal aberrations associated with either whole DNA copy number alterations or incomplete segmental alterations have also been shown to predict NB behaviour.…”
Section: Introductionmentioning
confidence: 99%